Paired Siglec receptors generate opposite inflammatory responses to a human‐specific pathogen. (18th January 2017) - Schwarz, Flavio; Landig, Corinna S; Siddiqui, Shoib; Secundino, Ismael; Olson, Joshua; Varki, Nissi; Nizet, Victor; Varki, Ajit
Abstract: Paired immune receptors display near‐identical extracellular ligand‐binding regions but have intracellular sequences with opposing signaling functions. While inhibitory receptors dampen cellular activation by recognizing self‐associated molecules, the functions of activating counterparts are less clear. Here, we studied the inhibitory receptor Siglec‐11 that shows uniquely human expression in brain microglia and engages endogenous polysialic acid to suppress inflammation. We demonstrated that the human‐specific pathogen Escherichia coli K1 uses its polysialic acid capsule as a molecular mimic to engage Siglec‐11 and escape killing. In contrast, engagement of the activating counterpart Siglec‐16 increases elimination of bacteria. Since mice do not have paired Siglec receptors, we generated a model by replacing the inhibitory domain of mouse Siglec‐E with the activating module of Siglec‐16. Siglec‐E16 enhanced proinflammatory cytokine expression and bacterial killing in macrophages and boosted protection against intravenous bacterial challenge. These data elucidate uniquely human interactions of a pathogen with Siglecs and support the long‐standing hypothesis that activating counterparts of paired immune receptors evolved as a response to pathogen molecular mimicry of host ligands for inhibitory receptors. Synopsis: Escherichia coli K1 uses its polysialic acid capsule to interact with Siglec‐11 and hijack its immune‐inhibiting function, but this is counteracted by the activating Siglec‐16. Siglec‐11 and Siglec‐16 are paired receptors expressed on innate immune cells, including brain microglia in humans only. The human‐specific pathogen Escherichia coli K1 interacts with Siglec‐11 via its polysialic acid capsule. Survival of E. coli K1 is increased or decreased upon interaction with Siglec‐11 or Siglec‐16, respectively. Paired Siglec receptors modulate inflammatory responses in vivo in a mouse model with engineered expression of activating Siglecs. Abstract : Escherichia coli K1 uses its polysialic acid capsule to interact with Siglec‐11 to escape host immune responses, but this is counteracted by the activating Siglec‐16.